The Presidents and the Constitution, Volume One : From the Founding Fathers to the Progressive Era. - Gormley, Ken (New York University Press, 2020)
Shines a light on the constitutional issues that confronted and shaped each presidency from George Washington to the Progressive EraDrawing from the monumental The Presidents and the Constitution: A Living History, published in 2016, the nation's foremost experts in the American presidency and the US Constitution join together to tell the intertwined stories of how the first twenty-seven distinctive American presidents have confronted and shaped the Constitution and thus defined the most powerful office in human history.From George Washington to William Howard Taft, The Presidents and the Constitution, Volume 1 illuminates the evolving American presidency in a unique way--through the lens of the Constitution itself. Arranged chronologically by president, the book examines the constitutional issues confronting each president in the context of the personalities driving historical events.The contributors illustrate the extensive powers of the American presidency in domestic and foreign affairs, showing how they have been used by the men who were granted them, and brings to light the overarching constitutional themes that span this country's history and tie each presidency to the other branches of government.